A Case Report of Aicardi-Goutières Syndrome Type 7 Caused by IFIH1 Gene Mutation and a Literature Review - ZHAO Min; SHU Zhou; HAN Tongxin; FU Yanhua; GAO Tianji; MAO Huawei (罕见病研究)
ObjectiveTo explore the clinical and genetic features of Aicardi-Goutières syndrome (AGS) caused by IFIH1 gene mutation.MethodsWe analyzed the clinical features and genetic mutation results of a boy with AGS type 7 and conducted a retrospective review of the literature of the characteristics and clinical features of IFIH1 gene mutations in AGS type 7.ResultsIn the case of this report, the patient, 13-year-old boy, exhibited gait abnormalities at age 3. As the condition was progressive, the boy has paraplegia of the lower limbs. The first brain MRI showed no lesions.Rehabilitation therapy in the past several years has shown no improvement.Recent brain CT revealed multiple intracranial calcifications. The whole-exome sequencing identified a heterozygous mutation in the IFIH1 gene (c.2159G > A, p.R720Q)- a known pathogenic mutation. Through review of the literature, we identified 69 cases of AGS type 7 (including the case reported here)which showed that skin and neurological system involvement are most commonly seen. Among these 69 patients, there were 30 different mutations in the IFIH1 gene, all of which are missense mutations. Seven patients had the same gene mutation as the boy in this study does, but their clinical features differed. In terms of treatment, Janus kainase(JAK) inhibitors are commonly used.Additionally, recent reports showed that tocilizumab treatment have been used for this condition.ConclusionsAGS7 is a type of I interferonopathy. Growth retardation and nervous system involvement are the most prevalent.The condition usually involve the skin, blood system, digestive system, kidney, heart, and other organs. JAK inhibitors prove effective for this disease.